BIOMASSA DAN KARBON POHON DI ATAS PERMUKAAN TANAH DI DATARAN TINGGI PADA KAWASAN TAMAN NASIONAL LORE LINDU (Studi Kasus Desa Sedoa Kecamatan Lore Utara Kabupaten Poso) - Idris, M. Fadli; Hamzari, Hamzari; Arianingsih, Ida (Jurnal Warta Rimba, 2017)
Global warming is climate change caused by the concentration of greenhouse gas emissions in the form of CO2, CH4, and other forms of excess in the atmosphere. The gas comes from the burning of fossil fuels, forest fires, forest conversion and other activities that led to the reduction in vegetation cover (deforestation and degradation) which in turn causes a decreases in carbon sequestration. National park is a nature conservation area which has original ecosystem, managed by a zoning system which is utilized for research, science, education, cultivation support, tourism and outdoor recreation. National park laid out in the core zone, wilderness zone, and the utilization zone. The aim of this research was to determine the large amount of biomass and carbon stored in the trees the surface of land in the highlands of Lore Lindu National Park, Sedoa Village, Sub-district Lore Utara, District Poso. The collection of sample data using plot biomass samples were analyzed using alometric equations. From the results of biomass of trees in the surface of land at an altitude plot of 1200 meters Lore Lindu National Park is 8708,47 tons/ha. At an altitude plot of 1400 meters Lore LinduÂ  National Park is 4922,28 tons/ha and at an altitude plot of 1600 meters Lore Lindu National Park is 3454,8 tons/ha. Carbon trees in the surface of land at an altitude plot of 1200 meters Lore Lindu National Park is 4354,24 tons/ha. At an altitude plot of 1400 meters Lore Lindu National Park is 2461,14 tons/ha and at an altitude plot of 1600 meter Lore Lindu National Park is 1729,9 tons/ha.Key Words: Biomass, Carbon, National Parks, Lore Lindu